2015
DOI: 10.15740/has/au/10.1/17-22
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of different sources and channels of agriculture information as perceived by the ber growers

Abstract: Credibility of information sources and channels affect the adoption of improved agricultural practices by farmers. Credibility refers to perceived trustworthiness and expertise accorded to a source or channel by its audience at any given time. Therefore, sources and channels of agriculture information play major role in diffusion of agriculture innovations. This study was conducted in Chomu tehsil of Jaipur district of Rajasthan, from Chomu tehsil ten villages were selected on the basis of highest area and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Meena, (2010) found that scientists and extension officers were perceived as most credible by farmers in Sriganganagar district of Rajasthan of India. Dhayal & Bochalya, (2015) reported that 'agriculture supervisor' was the most credible personal cosmopolite sources by the ber growers in Rajasthan of India. The extent to which the information and recommendations of communicators are accepted by farmers depends on their perception of the credibility of communicators as sources of information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meena, (2010) found that scientists and extension officers were perceived as most credible by farmers in Sriganganagar district of Rajasthan of India. Dhayal & Bochalya, (2015) reported that 'agriculture supervisor' was the most credible personal cosmopolite sources by the ber growers in Rajasthan of India. The extent to which the information and recommendations of communicators are accepted by farmers depends on their perception of the credibility of communicators as sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of credibility of information sources will be of immense value to the change agent or extension workers as it will help in appropriate planning of the communication strategy which may result in the quick acceptance of improved technology on the part of the farmers (Kapse & Chole, 2008). Dhayal & Bochalya, (2015) reported that credibility of information sources and channels affect the adoption of improved agricultural practices by farmers.…”
Section: Introductionmentioning
confidence: 99%
“…He defines Credibility of a particular agricultural information channel as the degree to which a source or channel is perceived as trustworthy and competent by the receiver. Thus, credibility of information sources and channels affect the adoption of improved agricultural and allied practices by farmers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers postulate that the credibility of information sources or channels affects how farmers adopt an agricultural innovation (Wilkins et al, 2018). Also, credible sources and channels play a significant role in disseminating agricultural information (Choudhary & Khan, 2017;Dhayal & Bochalya, 2015).…”
Section: Source Credibility Theorymentioning
confidence: 99%